My Health Too: Investigating the Feasibility and the Acceptability of an Internet-Based Cognitive-Behavioral Therapy Program Developed for Healthcare Workers - Bureau, Raven; Bemmouna, Doha; Faria, Clara Gitahy Falcao; Goethals, Anne-Aline Catteau; Douhet, Floriane; Mengin, Amaury C.; Fritsch, Aurélie; Zinetti Bertschy, Anna; Frey, Isabelle; Weiner, Luisa (Frontiers in Psychology, 2021)
Background: The COVID-19 crisis has had a considerable mental health impact on healthcare workers. High levels of psychological distress are expected to have a significant impact on healthcare systems, warranting the need for evidence-based psychological interventions targeting stress and fostering resilience in this population. Online cognitive behavioral therapy (CBT) has proved to be effective in targeting stress and promoting resilience. However, online CBT programs targeting stress in healthcare workers are lacking. Objective: The aim of our study is to evaluate the feasibility and acceptability of an internet-based CBT intervention, the My Health Too program we developed during the first COVID-19 epidemic peak in France. Methods: We recruited 10 participants among Alsace region hospital staff during the first peak of the pandemic in France. They were given one week to test the website and were then asked to answer an internet survey and a semi-structured phone interview. Results: We conducted a thematic analysis of the content from the phone interviews. Major themes were identified, discussed and coded: the technical aspects, the content of the website and its impact on participants’ emotions and everyday life. Overall, the participants reported finding the website easy to use and interactive. They described the resources as easy to understand, readily usable, and useful in inducing calm and in helping them practice self-compassion. Conclusions: Our results suggest that the My Health Too online CBT program is highly feasible and acceptable to healthcare workers during the highly stressful times of the pandemic peak. The feedback provided helped to improve the program whose efficacy is to be tested.